Comparative Study of Grade Cold Rolled Grain Oriented as The Core of A 3 Phase 200 kVA Distribution Transformer Using Ansys Maxwell - Huvat, Alexander; Rajagukguk, Managam; A. Gani, Usman (Faculty of Engineering, Universitas Tanjungpura, 2024)
This research discusses a comparative analysis of Cold Rolled Grain Oriented (CRGO) material as the core of a 3-phase 200 kVA distribution transformer using Ansys Maxwell software. CRGO material has several grades, namely M-3, M-4, M-5, and M-6, which differ in lamination thickness and core loss characteristics. The study aims to analyze and compare the flux density and core losses of the transformer with each CRGO grade. Simulations were conducted using Ansys Maxwell to compare flux density and losses for each CRGO grade to determine the most efficient material for use as a transformer core. The simulation results show that flux density increases over time across all tested CRGO grades, with grade M-3 exhibiting the highest flux density, followed by M-4, M-5, and the lowest being M-6. The simulation results for core losses are as follows: 226.2172 W for grade M-3, 242.1566 W for grade M-4, 259.2061 W for grade M-5, and 298.1239 W for grade M-6. Hysteresis and eddy current losses tend to be lower in lower-grade CRGO (M-3) compared to higher-grade CRGO (M-4, M-5, and M-6) due to the smaller lamination thickness in lower grades and larger lamination thickness in higher grades.